2007
DOI: 10.1088/0031-9155/52/13/019
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a commercial optical 3D surface imaging system for realignment of patients for radiotherapy of the thorax

Abstract: Accurate and reproducible patient setup is a prerequisite to fractionated radiotherapy. To evaluate the applicability and technical performance of a commercial 3D surface imaging system for repositioning of breast cancer patients, measurements were performed in a rigid anthropomorphic phantom as well as in healthy volunteers. The camera system records a respiration-gated surface model of the imaged object, which may be registered to a previously recorded reference model. A transformation is provided, which may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 20 publications
4
90
0
3
Order By: Relevance
“…Surface imaging is capable of providing full 3D monitoring of patient position in near real time. The commercially available AlignRT (VisionRT, London, UK) 3D surface imaging system has shown the abilities to detect submillimeter changes in patient position 10 , 12 , 13 , 14 , 15 , 16 , 17 and to accurately localize breast patients for free breathing 18 , 19 , 20 , 21 and deep inspiration breath‐hold treatments 22 , 23 to better than 5 mm. These works have shown that AlignRT is capable of accurately and reproducibly positioning breast tissue relative to treatment isocenter for initial patient positioning and, prior to beam‐on, for breath‐hold treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Surface imaging is capable of providing full 3D monitoring of patient position in near real time. The commercially available AlignRT (VisionRT, London, UK) 3D surface imaging system has shown the abilities to detect submillimeter changes in patient position 10 , 12 , 13 , 14 , 15 , 16 , 17 and to accurately localize breast patients for free breathing 18 , 19 , 20 , 21 and deep inspiration breath‐hold treatments 22 , 23 to better than 5 mm. These works have shown that AlignRT is capable of accurately and reproducibly positioning breast tissue relative to treatment isocenter for initial patient positioning and, prior to beam‐on, for breath‐hold treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, this alignment is performed in a two-step procedure, comprising (1) manual coarse patient setup using laser cross-hairs and skin markers, and (2) position verification and refinement using radiographic imaging. Over the past years, systems for non-radiographic patient setup and monitoring in RT have been proposed using different RI technologies, including active stereo vision [9], ToF imaging [10], structured light [8,11,12], and light sectioning [13,14]. These systems estimate the rigid transformation that aligns the intra-fractionally acquired external body surface of the patient with a given reference shape extracted from tomographic planning data.…”
Section: Positioning and Motion Management In Radiation Therapymentioning
confidence: 99%
“…This transformation can then be transferred to the treatment table control for automatic positioning. The focus of early solutions was on setup verification, restricting the automatic patient alignment to a fine-scale positioning and thus still requiring a manual setup initialization [9,13]. The first ToF-based systems for automatic patient setup in RT were proposed by Schaller et al [15] and Placht et al [10].…”
Section: Positioning and Motion Management In Radiation Therapymentioning
confidence: 99%
“…The advantages of the AlignRT system are its provision of real‐time tracking of patient surface location by monitoring of a region of interest during radiation therapy, its noninvasive imaging methodology, and its delivery of no extra radiation dose. It has been reported by multiple studies 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 that AlignRT can be an effective image guidance method for certain sites of radiation therapy treatment, including breast, intracranial stereotactic radiosurgery, thorax, and prostate.…”
Section: Introductionmentioning
confidence: 99%